The Trade Access of Latin American Exports UnderDebate. - Albertoni, Nicolás; Iturralde, Agustín; Correa, Ramiro; Eilender, Deborah; López, Ignacio (Latin American Journal of Trade Policy, 2025)
This paper presents the 2024 update of the Trade Vulnerability Index (TVI), developed by the Center for Development Studies (CED), as a tool for comparing the international integration of Latin American countries. Findings show that Mercosur remains behind in expanding its trade agreements, resulting in persistently high vulnerability levels, while Pacific countries (Australia, Chile, New Zealand, and Peru) exhibit more successful trade strategies. In the case of Uruguay, despite strong export performance, its growing reliance on markets without trade agreements increases structural vulnerability. A counterfactual exercise reveals that a potential agreement with China would have the most significant impact in reducing vulnerability, followed by the European Union, whereas the effect of an EFTA agreement would be marginal. Results confirm that the quality of international insertion depends not only on diversification but also on preferential market access, highlighting the urgent need for proactive, evidence-based trade policies.